Development E-Book Learning Media Based on Kvisoft Flipbook Maker - Fadillah, Ahmad; Nopitasari, Dian; Bilda, Westi (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2021)
The main purpose of this research is to produce a kvisoft flipbook maker-based ebook learning media product on root material, rank, and logarithms. The research carried out is development research (Development Research) with the ADDIE model. The sample in this study was a student of class X SMK Avicena Rajeg Tangerang Regency in 2021. The data in the study was collected using questionnaires, which consist of expert validation questionnaires, and student response questionnaires. Based on the results of the analysis of research data conducted obtained a value of 76% for media experts and 75.75% for material experts with good categories. The next stage is a practicality test and questionnaire on a small scale and obtained a score of 75.25% with good and practical categories. So it was concluded that the kvisoft flipbook maker-based ebook learning medium is feasible and practically used in math learning.Tujuan utama penelitian ini adalah untuk menghasilkan produk media pembelajaran ebook berbasis kvisoft flipbook maker pada materi akar, pangkat, dan logaritma. Penelitian yang dilaksanakan adalah penelitian pengembangan (Development Research) dengan model ADDIE. Sampel pada penelitian ini adalah siswa kelas X SMK Avicena Rajeg Kabupaten Tangerang tahun 2021. Data dalam penelitian ini dikumpulkan dengan menggunakan angket, yang terdiri dari angket validasi ahli, dan angket respon siswa. Berdasarkan hasil analisis data penelitian yang dilakukan diperoleh nilai 76% untuk ahli media dan 75,75% untuk ahli materi dengan kategori yang baik. Tahap berikutnya adalah tes kepraktisan dan kuesioner dengan skala kecil dan memperoleh nilai 75,25% dengan kategori baik dan praktis. Jadi disimpulkan bahwa media pembelajaran ebook berbasis kvisoft flipbook maker layak dan praktis digunakan dalam pembelajaran matematika.